PELATIHAN MANAJEMEN KEWIRAUSAHAAN BUMDES SEBAGAI PENGELOLA EKOWISATA HUTAN DESA GALUNGAN KABUPATEN BULELENG - Wahyuni, Ni Made; Sara, I Made (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Human resources are needed in developing the competitiveness. Galungan Village, Sawan District, Bali Province with assets in the form of village forests surrounded by mountains and beautiful natural scenery, cool air, jogging tracking, tours to waterfalls, rivers and hundreds of hundreds of years old trees are very worthy of being preserved as ecotourism icons. Based on the Decree of the Governor of Bali Number 2017/03-L/HK.2015 concerning the granting of village forest management rights, the management of village forest work areas is carried out by Rural-Owned Enterprises (BUMDes). The problem is that the performance of BUMDes: (1) low entrepreneurial intentions, attitudes, behavior; (2) low management practices (Aryaningsih, 2020). Business performance influenced by management, entrepreneurial attitudes. Objectives: 1) improve the implementation of entrepreneurial 2) improve the dissemination of management knowledge for institutional strengthening of Rural-Owned Enterprises. The method of implementing community service with a participatory method is through lectures, training, education that allows the service team to interact, communicate intensively and directly with the community and their business activities. Activities contribute to increasing knowledge and skills of BUMDes entrepreneurial management of village forest ecotourism. Suggestions, BUMDes managers and stakeholders pay more attention to management and entrepreneurial action in managing village forest ecotourism.